Thromboinflammation and Vascular Dysfunction - Karbach, Susanne; Lagrange, Jérémy; Wenzel, Philip (Hämostaseologie, 2019)
Thromboinflammation and vascular dysfunction are inseparably combined with the innate and the adaptive immune response. While the role of this interplay has gained considerable attention in the arena of atherosclerosis/atherothrombosis and in deep vein thrombosis, its role in other forms of vascular disease and risk factors is currently emerging. In this brief review, we will focus on thromboinflammation with regard to cytokine signalling as well as on the novel role of a vascular coagulation-inflammatory circuit in arterial hypertension.
Keywords: immune cells; cytokines; vascular dysfunction; atherosclerosis; inflammation; thrombosis; coagulation cascade